Best practice in primary care pathology: review 13. Issue 2 (28th October 2011) - Cabrera-Abreu, J C; Smellie, W S A; Bowley, R; Shaw, N
Abstract : This 13th best practice review examines tumour marker requesting primary care situations. The review is presented in question–answer format, referenced for each question. This review considers carcinoembryonic antigen carbohydrate antigen 15-3 (Ca15-3) and carbohydrate antigen 19-9 (Ca19-9). The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They will be updated periodically to take account of new information.